Stellar parameters for the central star of the planetary nebula PRTM 1 using the German Astrophysical Virtual Observatory service TheoSSA - Rauch, Thomas; Demleitner, Markus; Hoyer, Denny; Werner, Klaus (Arxiv, 2018)
The German Astrophysical Virtual Observatory (GAVO) developed the registered service TheoSSA (theoretical stellar spectra access) and the supporting registered VO tool TMAW (Tuebingen Model-Atmosphere WWW interface). These allow individual spectral analyses of hot, compact stars with state-of-the-art non-local thermodynamical equilibrium (NLTE) stellar-atmosphere models that presently consider opacities of the elements H, He, C, N, O, Ne, Na, and Mg, without requiring detailed knowledge about the involved background codes and procedures. Presently, TheoSSA provides easy access to about 150000 pre-calculated stellar SEDs and is intended to ingest SEDs calculated by any model-atmosphere code. In the case of the exciting star of PRTM 1, we demonstrate the easy way to calculate individual NLTE stellar model-atmospheres to reproduce an observed optical spectrum. We measured Teff = 98000 +/- 5000 K, log (g / cm/s**2) = 5.0 (+0.3/-0.2) and photospheric mass fractions of H = 7.5 x 10**-1 (1.02 times solar), He = 2.4 x 10**-1 (0.96), C = 2.0 x 10**-3 (0.84), N = 3.2 x 10**-4 (0.46), O = 8.5 x 10**-3 (1.48) with uncertainties of +/- 0.2 dex. We determined the stellar mass and luminosity of 0.73 (+0.16/-0.15) Msun and log (L / Lsun) = 4.2 +/- 0.4, respectively.
V1 4. Januar 2018, V2 8. Januar 2018
Gesehen am 14.03.2018